Pengaruh Kedisiplinan Dan Lingkungan Kerja Terhadap Kinerja - Nurnandiroh, Ika Anis; , Edy Purwo Saputro, S.E., M.Si (2016)
The purpose of this study was to analyze the effect of Discipline and the Work Environment on Performance. The technique used in this study is a random sampling. So that the population in this study are employees CV. Sindunata. Ie total number of employees by 117, while the samples in this study were 62 employees of the Editors. To achieve the objectives of the research, an analytical tool used in this study validity, reliability, hypothesis testing, and analysis tools in this study is the classical assumption used by the test instrument using SPSS program 16:00. From the results of the t test in this study showed that all of the variables did not affect the performance of employees with each value t_hitung <t_tabel (1.796 <2.001) for the factors of discipline and work environment also does not give effect to the performance of employees with value t_hitung <t_tabel ( 1.992 <2.001). Based on F test result that discipline and work environment factors partially or willing to jointly influence on employee performance CV. Sindunata, with a value F_hitung> F_tabel (4.137> 3.15).